2022
DOI: 10.1093/plphys/kiac089
|View full text |Cite
|
Sign up to set email alerts
|

The evolutionary history of small RNAs in Solanaceae

Abstract: The Solanaceae or “nightshade" family is an economically important group with remarkable diversity. To gain a better understanding of how the unique biology of the Solanaceae relates to the family’s small RNA genomic landscape, we downloaded over 255 publicly available small RNA datasets that comprise over 2.6 billion reads of sequence data. We applied a suite of computational tools to predict and annotate two major small RNA classes: (1) microRNAs (miRNAs), typically 20- to 22-nt RNAs generated from a hairpin… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
20
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 13 publications
(24 citation statements)
references
References 100 publications
4
20
0
Order By: Relevance
“…A vast majority of retroelements belonged to the long‐terminal repeat (LTR) Gypsy family, followed in abundance by the LTR Copia family. This is consistent with previous studies done in Solanaceae (Baldrich et al, 2021 ; Galindo‐González et al, 2017 ). While acknowledging that this analysis is likely not exhaustive, we note that due to the repetitiveness of these features, the study is sufficient to identify the sRNAs that originate from transposable elements.…”
Section: Resultssupporting
confidence: 93%
See 1 more Smart Citation
“…A vast majority of retroelements belonged to the long‐terminal repeat (LTR) Gypsy family, followed in abundance by the LTR Copia family. This is consistent with previous studies done in Solanaceae (Baldrich et al, 2021 ; Galindo‐González et al, 2017 ). While acknowledging that this analysis is likely not exhaustive, we note that due to the repetitiveness of these features, the study is sufficient to identify the sRNAs that originate from transposable elements.…”
Section: Resultssupporting
confidence: 93%
“…To analyze the expression of each of these PHAS loci, heatmaps for all four PHAS categories were generated. Results showed that among the 21‐nt PHAS loci that overlapped with coding genes (Figure 4a ), 25 were disease resistance genes, five were kinases, and one was DCL2, consistent with previous reports for other plant species (Baldrich et al, 2021 ; Fei et al, 2015 ; Reyes‐Chin‐Wo et al, 2017 ). We also observed a cluster of 20 loci that are highly expressed in all tissues, as well as two that appear to be flower specific (RHC10H1G1729.2 ‐ Basic chitinase and RHC08H2G1411.2 ‐ Pectinacetylesterase), one tuber specific (RHC06H2G2216.2 ‐ methyl‐CPG‐binding domain 10), and one that appears to have a higher expression in all Eva tissues (RHC04H1G0134.2 ‐ unidentified function).…”
Section: Resultssupporting
confidence: 90%
“…Both the tubercles of O. aegyptiaca and the interface have considerable amounts of 22-nt sRNA, which seem to play a more dominant role than in any other species in our set ( Figure 1H ). The 22-nt sRNAs do not typically play a role in root tissues ( Herranz et al, 2015 ), and in some species are produced from clusters in response to viral infection ( Baldrich et al, 2022) . We could not detect the presence of viral-derived sRNAs in our Orobanche libraries compared to viral-infected samples ( Annacondia and Martinez, 2021 ) ( Supplemental Figure S2 ), indicating that these populations of 22-nt sRNAs were not produced in response to viral infection.…”
Section: Resultsmentioning
confidence: 99%
“…sRNA abundance is known to directly impact their functions (Bartel, 2009). Comparative studies on sRNA long‐time evolution from green algae to flowering plants have been widely reported (Ma et al., 2010; Cuperus et al., 2011; Chavez Montes et al., 2014; Zheng et al., 2015; Lunardon et al., 2020; Baldrich et al., 2022). However, the role of sRNAs in crop domestication (shorter evolutionary time) and whether and how crop domestication affects sRNA dynamics have not been systematically investigated.…”
Section: Discussionmentioning
confidence: 99%
“…Comparative studies on miRNA gene evolution in Arabidopsis lyrata and A. thaliana that diverged more than 10 million years ago have discovered numerous less conserved miRNA genes exhibiting high divergence in hairpin structures, processing fidelity, and target complementarity (Ma et al., 2010; Cuperus et al., 2011). With the increasing number of analyses on sRNA sequencing (sRNA‐seq) data, more and more less conserved miRNAs and phasiRNA‐generating loci (PHASs) have been uncovered in diverse species, from green algae to flowering plants (Chavez Montes et al., 2014; Zheng et al., 2015; Lunardon et al., 2020; Baldrich et al., 2022; Chen et al., 2021; Guo et al., 2022). However, whether and how the expression patterns and functions of sRNAs have been changed in shorter evolutionary times such as during crop domestication is unknown.…”
Section: Introductionmentioning
confidence: 99%